On the distribution of Percnon gibbesi (H. Milne Edwards, 1853) (Crustacea, Decapoda, Plagusiidae) along the Tunisian coast - SGHAIER, Y.R.; ZAKHAMA-SRAIEB, R.; CHARFI-CHEIKHROUHA, F. (Mediterranean Marine Science, 2011)
The subtropical crab, Percnon gibbesi is established along the Tunisian coasts. This crab was recorded by underwater observation from Malloula, Tabarka, El-Haouaria, Yasmine Hammamet, Monastir marina and the Kuriat Islands. These new observations increase the known distribution of P. gibbesi in the south Mediterranean basin.